Alteration in the cytokine levels and histopathological damage in common carp induced by glyphosate. (June 2015) - Ma, Junguo; Li, Xiaoyu
Highlights: Glyphosate has low toxicity on common carp. Glyphosate-exposure alters the contents of cytokines. Glyphosate caused histopathological damage to common carp. Glyphosate has immunotoxic effects on common carp. Abstract: Glyphosate is one of the most frequently used herbicides, and it has been demonstrated to generate a series of toxicological problems in animals and humans. However, relatively little is known about the effects of glyphosate on the immune system of fish. In the present study, the acute toxicity of glyphosate on common carp was first determined; then, the contents of interferon-γ (IFN-γ), interleukin-1β (IL-1β), and tumor necrosis factor -α (TNF-α) and histopathological alterations in the liver, kidneys, and spleen of common carp exposed to 52.08 or 104.15 mg L −1 of glyphosate for 168 h were also determined and evaluated. The results of the acute toxicity tests showed that the 96 h LC50 of glyphosate for common carp was 520.77 mg L −1 . Moreover, sub-acute exposure of glyphosate altered the contents of IFN-γ, IL-1β, and TNF-α in fish immune organs. For example, there was a remarkable increase in the IFN-γ content in the kidneys, while there was a decrease in the liver and spleen. The IL-1β content increased in liver and kidneys, but it decreased in the spleen, and TNF-α mainly increased in the fish liver, kidneys, and spleen. In addition, glyphosate-exposure also caused remarkable histopathological damage in the fish liver, kidneys, and spleen. These results suggest that glyphosate-caused cytokine alterations may result in an immune suppression or excessive activation in the treated common carp as well as may cause immune dysfunction or reduced immunity. In conclusion, glyphosate has immunotoxic effects on common carp.